Relationships between monocyte count to high-density lipoprotein cholesterol ratio and cardiovascular outcomes in patients commencing dialysis - Dongryul Kim (SAGE Publishing, 2021)
Objective High monocyte to high-density lipoprotein cholesterol ratio (MHR) is known to be a risk factor for cardiovascular (CV) complications. We aimed to evaluate the relationship between MHR and CV outcomes in patients commencing dialysis. Methods The medical records of patients who started maintenance dialysis between January 2006 and July 2017 were reviewed. The primary outcomes were all-cause mortality and overall CV mortality and the secondary outcomes were CV event-free survival and the incidence of CV complications. Results Five hundred ninety-seven patients were enrolled and allocated to low- or high-MHR groups. All-cause mortality did not differ between the groups during a mean follow-up period of 3.9 years. In addition, overall CV mortality did not differ between the groups. However, CV event-free survival was significantly lower in the high-MHR group than in the low-MHR group (47.5% vs . 59.0%). Multivariate Cox regression analysis showed that high MHR was an independent predictor of CV events (HR 1.886, 95% CI 1.015–3.505). Conclusion High MHR at the time of initiation of dialysis may represent a useful predictor of CV complications.